The Effect of Product Quality, Product Price, and Brand Image on the Interest in Purchasing a Car at Toyota Auto2000 Cirebon - Panca Nugraha; Ramlah Puji Astuti; Soesanty Maulany (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study aims to analyze the effect of product quality, product price, and brand image on consumers' interest in purchasing cars at Toyota Auto2000 Cirebon. Design/methodology/approach: The study used an associative quantitative approach with an explanatory research design. Data were collected through a Likert scale questionnaire administered to 100 respondents using simple random sampling. Analysis was performed using multiple linear regression through SPSS, including validity, reliability, classical assumptions, t-test, and F-test. Findings: The results show that product quality, product price, and brand image have a positive and significant effect on purchase intention, both partially and simultaneously. Research limitations/implications: The study was limited to one dealer and a specific period of time, so generalizations are still limited. Practical implications: The results of this study can be used as a basis for formulating marketing strategies to increase consumer purchase intention. Originality/value: This study integrates product quality, price, and brand image into a single empirical model in the context of local automotive dealers. Paper type: Research paper